Delivering Inclusive Cultural Offers for Social Prescribing: A Realist Evaluation Involving Older People From Global Majority Backgrounds and Cultural Sector Providers in the UK. - Westlake, Debra; Mahtani, Kamal R.; Wong, Geoffrey; Gorenberg, Jordan; Santillo, Marta; Husk, Kerryn; Vougioukalou, Sofia; Baxter, Ruthanne; Dawson, Shoba; Potter, Caroline M.; Warburton, Harriet; McDougall, Beth; et al. (Health Expectations, 2026)
Introduction: Research shows cultural activities benefit older people's wellbeing, but little is known about why individuals from global majority (minority ethnic) groups engage less with the mainstream cultural sector, or how it could adapt to meet their needs and encourage engagement. The TOUS study (Tailoring cultural Offers with and for diverse older Users of Social prescribing) investigated the question: What tailoring is needed, how, when and for whom, to optimise cultural offers as part of social prescribing for older people (aged 60+) from global majority groups? Methods: The TOUS study involved focused ethnographies with six cultural‐sector organisations throughout the United Kingdom and 11 key informant interviews with cultural providers. A realist approach was adopted, resulting in the development of a programme theory. Results: The programme theory has three pillars: (1) broker, hook, and opportunity, which support entry into cultural spaces to provide immediate benefits; (2) safety and trust, power‐sharing, and meaning, which sustain engagement; and (3) transformative outcomes, including lasting relationships, confidence, and exploring identities. Conclusions: With intentional engagement and relational practices, organisations can foster inclusive cultural participation and support well‐being in later life. Patient or Public Contribution: The TOUS study was guided by a public involvement group of six contributors (aged 60+ from global majority/minority ethnic backgrounds) who shared experiences of creative practice, and advised on data collection, analysis, model development, and dissemination. The study also involved collaborative analysis of data at case sites.